1994
DOI: 10.1159/000119156
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Findings of Negative Symptoms in Schizophrenia and Their Putative Relevance to Pharmacological Treatment

Abstract: The most prominent biochemical finding in schizophrenic patients with negative symptoms appears to be the reduction in central dopaminergic, serotoner-gic and noradrenergic activity. This decrease in amine activity tends to be associated with structural brain abnormalities, i.e., cortical atrophy or enlarged ventricles. There are indications that typical neuroleptics reduce those negative symptoms of schizophrenia that are secondary to positive symptoms when these are effectively treated. However, negative sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…In addition, Van Kammen et al (1986) has reported the occurrence of decreased noradrenaline and MHPG concentrations in the cerebrospinal fluid (CSF) of schizophrenic patients with negative symptoms. Therefore, these negative symptoms may be attributable to dysfunction of the prefrontal cortex, including hypofunction of the noradrenergic network (Rao and Moller 1994). To support this, idazoxan, a selective ␣2-antagonist, is reported to augment therapeutic effect of typical neuroleptics in treatment of schizophrenia (Litman et al 1993(Litman et al , 1996.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Van Kammen et al (1986) has reported the occurrence of decreased noradrenaline and MHPG concentrations in the cerebrospinal fluid (CSF) of schizophrenic patients with negative symptoms. Therefore, these negative symptoms may be attributable to dysfunction of the prefrontal cortex, including hypofunction of the noradrenergic network (Rao and Moller 1994). To support this, idazoxan, a selective ␣2-antagonist, is reported to augment therapeutic effect of typical neuroleptics in treatment of schizophrenia (Litman et al 1993(Litman et al , 1996.…”
Section: Discussionmentioning
confidence: 99%
“…This observation correlates with the activity of these compounds in behavioral tests for anxiolytic activity (see below) and may contribute to a favorable effect on negative symptoms. Antagonist activity at the serotonin 5-HTzA receptor has also been suggested to predict efficacy against negative symptoms (50,72). The high affinity of iloperidone for serotonin 5-HT2, receptors indicates that it should be effective against negative symptoms.…”
Section: In Viiro Receptor Bindingmentioning
confidence: 99%
“…Siris et al (1990) found that imipramine maintenance adjunctive to fluphenazine was superior to fluphenazine and placebo for preventing relapse into psychotic depression or negative symptom states. Monoamine oxidase inhibitors have also been suggested in the treatment of negative symptoms (Rao and Moller, 1994). The efficacy of adjunctive fluvoxamine for the treatment of negative symptoms of schizophrenia has been demonstrated in two clinical trials of 30 (Silver and Nassar, 1992) and 53 participants (Silver et al, 2000), respectively.…”
Section: Introductionmentioning
confidence: 99%